The Creation of the Original Text of the Epic "Alpomish" - Shakhnoza Kamaliddinovna Askarova (Journal of Higher Education and Academic Advancement, 2024)
In the article, there are many original and translated sources that have come down to us, but the content of which has not been sufficiently studied. The epics of the "Alpomish" series, which are widespread among the Turkic peoples, have attracted the attention of a large number of folklorists, linguists, literary scholars, philosophers, historians, and ethnographers due to their historical significance and artistic value.